Kajian Sistem Distribusi Air Bersih Berdasarkan Indikator Debit dan Tekanan Air Kpspams Kuro Sejahtera 1, Desa Kuro Kabupaten Oki - Muhamad Darmawan; Taufik Ari Gunawan; Imroatul C. Juliana (Syntax Corporation, 2023)
The clean water distribution system is generally a piping network consisting of a system of pipes, pumps, reservoirs and other equipment. With the existing treatment system and piping network system, the management in this case KPSPAMS Kuro Sejahtera 1 is expected to be able to meet the clean water needs of the community in Kuro Village, Pampangan District, Ogan Komering Ilir Regency. The purpose of this study is to contribute to the analysis of the clean water network for the village. It is hoped that the determination of the right analysis will serve the community well in terms of clean water needs for the development stage in Kuro Village, simulate the clean water distribution pipe network in Kuro Village using EPANET 2.0 software, and compare the results of the simulation of the clean water distribution pipe network using EPANET software. 2.0 with the results of the distribution pipeline system planning for the current condition. From the calculation results, it is found that the average daily requirement of 0.89 L/second is sufficient for the water production of KPSPAMS Kuro Sejahtera 1 which produces water of 1.9 L/second. Based on the simulation results, the pressure value for the peak hour of water usage is at 07.00 WIB, and the highest pressure is 11.90m while the lowest pressure is 0.11m.